Guatemalan government adopts local information system for the monitoring and early warning of climate-related seasonal hunger co-designed with CCAFS scientists - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
In 2018, the Guatemalan Secretariat for Food and Nutrition Security (SESAN) adopted an information system that supports the local food security monitoring and early warning in all 340 municipalities of the country. This adoption is an important step towards proactively managing food security and climate risks. CCAFS/Bioversity science and evidence on information preferences, decision-making processes and users needs supported the participatory co-design process of the system from developing the idea through prototyping to implementation.